Diagnostic Imaging of Musculoskeletal Diseases A Systematic Approach - Bonakdarpour, Akbar; Reinus, William R.; Khurana, Jasvir S.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2010)
With the advent of new technologies, the field of musculoskeletal radiology has grown to include not only diseases that affect the skeleton, but also those that affect muscles, ligaments, tendons and also the cartilaginous structures within joints. Diagnostic Imaging of Musculoskeletal Diseases: A Systematic Approach is a useful and worthy teaching text that is at once readable by the radiology resident rotating through the musculoskeletal radiology and thorough enough to be used by the practicing radiologist. Written by authors who are well established in the field of musculoskeletal radiology and pathology, this volume provides readers with a practical and systematic approach to think about diagnosis of pathologic conditions that affect the musculoskeletal system, thus making the material easier to learn and synthesize. Chapters are organized by major categories of disease: trauma, infection, tumors and tumor-like conditions, metabolic diseases, dysplastic diseases and arthritis. Additional chapters examine basic interventional techniques that apply to musculoskeletal imaging and in recognition of the importance of orthopedic procedures, information is included on the use, imaging, appearance, and pathology affecting prostheses and fixation devices. Diagnostic Imaging of Musculoskeletal Diseases: A Systematic Approach is an exceptionally important new text that contains information essential to the practice of modern radiology.
Bone Structure and Function -- Systematic Approach to Metabolic Diseases of Bone -- Systematic Approach to Radiology of Endocrine Disorders Affecting the Musculoskeletal System -- Circulatory Diseases of Bone and Adjacent Soft Tissues -- Imaging Approach to Musculoskeletal Trauma -- Imaging and Understanding Fracture Fixation -- Systematic Approach to Tumors and Focal Lesions of Bone -- Systematic Approach to Tumors and Tumor-Like Conditions of Soft Tissue -- Imaging Approach to Hemoglobinopathies -- Imaging Approach to Musculoskeletal Infections -- Systematic Approach to Arthropathies -- Imaging of Prostheses -- Systematic Approach to Skeletal Dysplasias with Emphasis on Non-lethal Disorders -- Interventional Procedures in Musculoskeletal Radiology.
Keywords: Medicine; Radiology, Medical; Pathology; Medicine & Public Health; Diagnostic Radiology; Pathology